2007
DOI: 10.1016/j.bcp.2006.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Inducible overexpression of c-Jun in MCF7 cells causes resistance to vinblastine via inhibition of drug-induced apoptosis and senescence at a step subsequent to mitotic arrest

Abstract: Abstractc-Jun is a major component of the AP-1 transcription factor and plays a key role in regulation of diverse biological processes including proliferation and apoptosis. Treatment of a wide variety of cells with the microtubule inhibitor vinblastine leads to a robust increase in c-Jun expression, JNKmediated c-Jun phosphorylation, and activation of AP-1-dependent transcription. However, the role of c-Jun induction in the response of cells to vinblastine remains obscure. In this study we used MCF7 breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Contrary to those observations, Poindessous-Jazat et al (2002) also showed that c-Jun overexpression inhibited serum deprivation-induced apoptosis in these cells. In addition, the studies of apoptosis induced in other cell types have implicated c-Jun protects cells against serum deprivation-induced or anticancer drug-induced cell death (Huang et al, 2000;Duan et al, 2007). These results suggest that c-Jun does not affect apoptosis or may function to modulate apoptosis either positively or negatively, depending on the microenvironment and the cell type.…”
Section: Discussionmentioning
confidence: 78%
“…Contrary to those observations, Poindessous-Jazat et al (2002) also showed that c-Jun overexpression inhibited serum deprivation-induced apoptosis in these cells. In addition, the studies of apoptosis induced in other cell types have implicated c-Jun protects cells against serum deprivation-induced or anticancer drug-induced cell death (Huang et al, 2000;Duan et al, 2007). These results suggest that c-Jun does not affect apoptosis or may function to modulate apoptosis either positively or negatively, depending on the microenvironment and the cell type.…”
Section: Discussionmentioning
confidence: 78%
“…Vinblastine also interferes with amino acid, cAMP, and glutathione metabolism, and can induce apoptosis through the nuclear factor kB/inhibitor of kB (NF-kB/IkB) pathway (Huang et al 2004). Apparently, c-Jun protects T47D cells from vinblastine-induced cell death, although it does not prevent the mitotic block (Duan et al 2007). At nontoxic doses, vinblastine inhibits chemotaxis and endothelial cell proliferation, highlighting its antiangiogenic properties (Vacca et al 1999).…”
Section: Properties Of Selected Chemotherapeutic Drugsmentioning
confidence: 99%
“…For example, whereas a dominant-negative to c-Jun rendered KB-3 cells more vinblastine-resistant , suggesting a proapoptotic role, c-Jun knockout fibroblasts, predicted to be more resistant, were equally as sensitive as wild-type cells (Obey et al, 2005). In addition, stable or inducible overexpression of c-Jun renders cells markedly resistant to vinblastine (Obey et al, 2005;Duan et al, 2007). These results may reflect cell type-specific differences in c-Jun function and probably reflect the fact that c-Jun plays a role in both cell proliferation and cell death and can functionally participate in many different protein complexes.…”
mentioning
confidence: 96%